The Long winter - Wilder, Laura Ingalls; Williams, Garth (London : Puffin, 1968)
The Ingalls family move their syore into town during the terrible winter of 1880, when food is scarce and they face storvation.
Keywords: Family life -- Fiction; Winter -- Fiction